Pengaruh Model Pembelajaran Problem Based Learning terhadap Berpikir Kritis Siswa SMP pada Pembelajaran Biologi Materi Pemanasan Global - Fitriyyah, Siti Jazilatul; Wulandari, Tabitha Sri Hartati (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
The demand of science learning in the global era according to the National Science Teachers Association (2006) is to prepare learners with a variety of skills and skills, one of which is critical thinking skills. In learning Biology in SMP Negeri 3 Kragan critical thinking skills have not been empowered by teachers. Efforts to improve the skills of critical thinking is with the model of learning Problem Based Learning. The purpose of this study to determine the effect of learning model Problem Based Learning on students' critical thinking skills. This research was conducted on the seventh grade students of SMP Negeri 3 Kragan. The material in this research is global warming. This type of research is a quasi-experimental research with Pretest-Posttest Control Group Design design. The sample in this research is VII A class (experimental class) and VII B class (control class), each class is 30 students. Data analysis using t test. The results showed that the average value of all aspects and indicators of critical thinking experimental class is higher than the control class. Percentage in experimental class 83,60% while in control class 76,40%. Data analysis with t test obtained sig value 0.000, so it is concluded that model of learning of Problem Based Learning influence to critical thinking skill of SMP Negeri 3 Kragan student on global warming material